Philosophical Remarks on City and Right to the City / Felsefede Kent ve Kent Hakkı - Guven, Ozguc; Kardes, Murat Ertan (The City's Language / Şehrin Dili / Langues de la ville, 2021)
A city forms the core of all political and philosophical projects. On one hand, a city is a place of human aspirations and pursuits; on the other, it represents a space of tension and anxiety. This dual and often paradoxical character of the city compels philosophers to constantly cogitate its current status. Philosophy is often defined as the child of the city (polis); it is thus the product of urban life. As a medium of social space and political unity, the city has become a stipulation for philosophical activity. In this sense, philosophy is not deprived of its conditions; alternatively, it is an activity that reveals itself within its prerequisite environment. The book reveals varied philosophical reflections on the city, focusing primarily on the urban crisis and debates on rights to the city. The book also attends to the city-philosophy connection in terms of language, borders, art, architecture, and meta-philosophy. The body of research on the city cannot be reduced to the sum of discourses of technical experts. Beyond this boundary, the city stands in its entirety at the heart of debates on equality, freedom, and liberation, surpassing all types of pragmatic discussion. Max Weber cites the proverb, "Stadtluft macht frei" (the urban air frees), serving as a reminder that a city is also a place of domination and freedom. In this respect, the city is the arena of all types of conflict.